2017
DOI: 10.1038/nature20792
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide in vivo screen identifies novel host regulators of metastatic colonization

Abstract: Metastasis is the leading cause of death for cancer patients. This multi-stage process requires tumour cells to survive in the circulation, extravasate at distant sites, then proliferate; it involves contributions from both the tumour cell and tumour microenvironment (‘host’, which includes stromal cells and the immune system1). Studies suggest the early steps of the metastatic process are relatively efficient, with the post-extravasation regulation of tumour growth (‘colonization’) being critical in determini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
173
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 191 publications
(176 citation statements)
references
References 48 publications
3
173
0
Order By: Relevance
“…Blocking the release of S1P through the genetic deletion of its extracellular transporter, S1P transporter spinster homologue 2 (Spns2) led to an increased infiltration of effector T cells and natural killer (NK) cells into the metastatic tumor site, lowering the metastatic burden. Since the target Sgpl1, identified and validated in our in vivo screens, directly and irreversibly degrades S1P and results in a similar phenotype, our findings are consistent with an impact of Sgpl1 knockdown on its immune stimulated phenotype [50]. Therefore, we hypothesize that knockdown of Sgpl1 works to enhance immune cell tumor destruction by increasing the microenvironment levels of S1P, leading to an increase in NK cell and CD8 T cell trafficking into the tumor.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Blocking the release of S1P through the genetic deletion of its extracellular transporter, S1P transporter spinster homologue 2 (Spns2) led to an increased infiltration of effector T cells and natural killer (NK) cells into the metastatic tumor site, lowering the metastatic burden. Since the target Sgpl1, identified and validated in our in vivo screens, directly and irreversibly degrades S1P and results in a similar phenotype, our findings are consistent with an impact of Sgpl1 knockdown on its immune stimulated phenotype [50]. Therefore, we hypothesize that knockdown of Sgpl1 works to enhance immune cell tumor destruction by increasing the microenvironment levels of S1P, leading to an increase in NK cell and CD8 T cell trafficking into the tumor.…”
Section: Discussionsupporting
confidence: 85%
“…We found that suppression of Sgpl1 had a significant, selective effect on resistance to anti-tumor immune attack in immune competent mice and that this effect is present in multiple TNBC lines and mouse strains. A recent report by van der Weyden et al identified a number of genes important for the metastasis of melanoma and TNBC cells in an immune competent setting [50]. They employed an in vivo RNA-seq metastasis screen in immune competent mice across a variety of cell lines and mouse strains, and identified the importance of sphingosine-1-phosphate (S1P) in local immune cell trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…3). Interestingly, deletion of Spns2 resulted in a marked reduction in lung metastasis after tail vein injections of various types of mouse cancer cells and was associated with circulating lymphopaenia and increased infiltration of T cells and natural killer cells to the lungs, therefore enhancing tumour cell killing and decreasing metastatic burden in Spns2 −/− mice 106 . These data were consistent with a study reporting the systemic roles of S1P as a transducer of host–cancer cell communication to induce metastasis of mouse bladder cancer or melanoma cells to the lungs of Sphk1 +/+ control mice, which was reduced in Sphk1 −/− mice 107 .…”
Section: S1p In Cancer Growth and Metastasismentioning
confidence: 99%
“…S1PR signalling inhibits apoptosis, induces cell proliferation and/or migration and increases drug resistance via inhibition of BAX–caspase 3 signalling, induction of survival autophagy and/or inhibition of serine/threonine-protein phosphatase 2A (PP2A) 104,105,136 . b | Circulating S1P increases tumour metastasis 106110 . For example, SPNS2-dependent S1P secretion from endothelial cells attenuates cytotoxic T cell function, possibly by influencing S1PR functions on immune cells 106 and/or cancer cells 107 , and therefore promotes tumour metastasis 106,107 .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation